PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP PERTUMBUHAN BEBERAPA BENIH ASAL KLON KAKAO (Theobroma cacao l.) DI PEMBIBITAN - Hasmawi Hasyim; Hadriman Khair; Ridho Ardinata (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study to determine the growth response of several types of clones of cocoa (Theobroma cacao L.) with an organic fertilizer in polybag. The design used was Randomized Design Group factorial with two factors were studied, namely: organic fertilizer factor which is denoted by the letter "O" and the stage is divided into 3 = without giving Oo, O1 = Amazing Bio Fertilizer Growth (ABG) and O2 = Super Bionic Fertilizer and Cocoa varieties factor denoted by the letter "K" is divided into three types: TSH 858 = K1, K2 = K3 = RCC 70 and PA 300. Organic fertilizer as the first factor and the varieties of cocoa as a second factor, while the parameters measured were plant height (cm), number of leaves (pieces), stem diameter (mm), leaf area (cm), root wet weight (g), weight wet bars (g), root dry weight (g), stem dry weight (g) and root volume (cc).Keywords:organic fertilizer, clone, cocoa, polybag